Ultra-short Laser Pulse Generated by a Microring Resonator System for Cancer Cell Treatment. (June 2013) - Jalil, M. A.; Ong, C. T.; Saktioto, T.; Daud, S.; Aziz, M. S.; Yupapin, P. P.
Abstract A microring resonator (MRRs) system incorporated with a add/drop filter is proposed in which ultra-short single, multi-temporal, and spatial optical soliton pulses are simulated and used to kill abnormal cells, tumors, and cancer. Chaotic signals are generated by a bright soliton pulse within a nonlinear MRRs system. Gold nanoparticles and ultra-short femtosecond/picosecond laser pulses' interaction holds great interest in laser nanomedicine. By using appropriate soliton input power and MRRs parameters, desired spatial and temporal signals can be generated over the spectrum. Results show that short temporal and spatial solitons pulse with FWHM = 712 fs and FWHM = 17.5 pm could be generated. The add/drop filter system is used to generate the high-capacity, ultra-short soliton pulses in the range of nanometer/second and picometer/second.